PENGARUH PENDAPATAN BAGI HASIL DAN FEE BASED INCOME TERHADAP LABA BERSIH (STUDI KASUS PADA BANK UMUM SYARIAH PERIODE 2018-2023) - Hasanah, Mauizatul; Zaroni, Akhmad Nur; Rahmatullah, Nur (Indonesian Scientific Journal of Islamic Finance, 2024)
Sharia banks operate to generate profits, in fact there are many factors that affect net profit, one of which isthe income and services provided by the bank. In this study, it aims to determine whether profit sharing income and fee-based income have a significant effect on net income. This study used a quantitative approach. In determining samples using purposive sampling techniques. The results showed that the variable profit sharing income had a partial significant effect on net profit by 15% while fee based income had a partial significant effect on net income by 45%, as well as simultaneously the variable profit sharing income and fee based income Significantly affects net profit by 59.4%, the rest is influenced by other variables. The analysis technique used is panel data regression analysis with the Eviews 12 tool.